Efficacy of Low-Level Laser Therapy in Reducing Pain in the Initial Stages of Orthodontic Treatment - Manoel Heitor Brito; Cinthya Quagliato Nogueira; Paula Cotrin; Tiago Fialho; Renata Cristina Oliveira; Ricardo Gobbi Oliveira; Samira Salmeron; Fabrício Pinelli Valarelli; Karina Maria Salvatore Freitas; Rodrigo Hermont Cançado (International Journal of Dentistry)
Purpose. There is no consensus about the mechanism and efficacy in alleviating pain of the lower-level laser therapy (LLLT) during orthodontic treatment. This study aimed to evaluate the LLLT effectiveness clinically in reducing pain caused by orthodontic movement that occurs in the early stages of treatment. Methods. The sample consisted of 54 patients in need of orthodontic treatment divided into two groups. A 28 experimental patients group (initial mean age: 26.84 years old) was undergone gallium-aluminum-arsenide infrared laser application on 12 points for each tooth immediately after the installation of the first alignment archwire, and a 26 patients control group (initial mean age: 29.13 years old) was undergone to no pain control intervention at all. Pain intensity was measured by using a visual analog scale, which was marked pain level (mm) reported in 06, 24, 48, and 72 hours. The perception of pain (beginning, peak, decline, and absence) was evaluated by filling up a questionnaire. To compare the intensity and perception of pain between groups, a nonparametric Mann–Whitney has been performed. Results. The experimental group showed levels (mm) at 6 (p<0.001), 24 (p=0.004), and 48 hours (p=0.007) and perception of pain (hours) in the peak (p=0.026), decline (p=0.025), and absence (p=0.008) significantly lower compared to the group control. Conclusion. Low-level laser therapy is effective in reducing pain severity caused by orthodontic forces activation, and it promotes the analgesic action lasting effect during the most painful feeling time.